Traffic analysis for video streaming : a study in FTMSK / Diana Mohd Alwi - Mohd Alwi, Diana (Faculty of Computer and Mathematical Sciences, 2005)
This research is all about the analysis of the network traffic flow in FTMSK in order to determine the rational implementing video streaming in FTMSK and also to determine the best video format that can accommodate with the traffic. The analysis was made on the network traffic at the main switch and router. In order to gather the data traffic, it requires the used of network analyzing tools such as Opmanager and PRTG Traffic Grapher 4.1.0.265 for Windows. These tools had been used to gather and analyze the data. Furthermore, there also software needed for streaming purpose such as streaming media players and streaming media encoders. As we know, video streaming need high speed of internet to increase throughput and take less time for streaming purpose. Therefore, by monitoring the network performance in FTMSK we can determine whether video streaming can be implemented and by using the best format of video.